Formulasi dan Uji Sifat Fisik Cairan Penyubur Rambut yang berupa Sediaan Hair Tonik Ekstrak Seledri: hairtonik - Ni Made Sukma Sanjiwani Sanjiwani; Sudiarsa I Wayan; Mirah Mariyati Ni Putu Ayu; Adelia Vinanda Ketut (Program Studi Pendidikan Matematika dan Pendidikan Biologi Universitas PGRI Mahadewa Indonesia, 2023)
Hair can prevented his loss with use hair tonic natural . One hair tonic naturally can prevent loss and fertilize hair is hair tonic extract celery . Study This own objective For know organoleptic from hair tonic extract celery in 3 formulations for 1 month in every week and for know pH value, density and viscosity of hair tonic extract celery in 3 formulations for 1 month in every the week. Making hair tonic extract celery made with way , extract thick celery weighed especially formerly using 3 formulations, each extract thick celery dissolved with ethanol Then mashed with mortar then added fluid tongue crocodile Then mashed again and lastly added aroma to each formulation furthermore mashed until homogeneous with mortar. Research results produce that extract thick celery and liquid tongue crocodile can formulated become a hair tonic with addition 96% ethanol and fragrance. However based on organoleptic data, pH, weight type all formulation hair tonic preparations and controls are also stable and already fulfil hair tonic requirements that can use on skin head . While on the value viscosity , the most satisfying formula condition stability are formulas 1 and 2 as well control with addition extract celery in formula 1 is 2 grams and formula 2 is 4 grams while in the control No There is addition extract celery .